Outcomes of high dose therapy and autologous haematopoietic stem cell transplantation for non‐hodgkin lymphoma: A retrospective analysis in a resource‐limited country. Issue 3 (28th November 2020) - Anuar, Nur Adila; Tey, Kevin Wen Fei; Ng, Soo Chin; Teh, Alan Kee Hean; Abdul Rahman, Mohd Haris Fadzillah; Chong, Bee Ping; Gan, Gin Gin
Abstract: Aim: To retrospectively report the clinical outcomes of non‐Hodgkin's Lymphoma (NHL) patients post high dose therapy (HDT) with autologous haematopoietic stem cell transplant (AHSCT) and determine whether upfront transplant, which is a first‐line consolidative treatment with induction chemotherapy, would be a feasible modality in a resource‐limited country. Methods: The medical records for NHL patients who had undergone HDT followed by AHSCT from October 1997 to November 2016 from two hospitals in Klang Valley, Malaysia were obtained from the medical record database and analysed retrospectively through statistical analysis. Results: A total of 148 patients were retrospectively identified post‐AHSCT, where the majority of whom had B cell lymphoma (53.4%). Majority of patients (88.5%) were in complete remission before AHSCT. The overall survival (OS) and event‐free survival (EFS) at 3 years were 68.9% and 60.8%, respectively. The major cause of death was disease progression at 73.9%, while transplant‐related mortality was 15.2%, with a median follow‐up period of 179.5 weeks. Conclusion: Our study illustrates the promising outcomes of HDT with AHSCT in NHL patients in a resource‐limited country. We recommend larger studies to be conducted in the future with a longer duration of follow‐up to validate our findings.